“Social Integration Empowerment”: Upaya Memperkuat Industrialisasi Bandeng Di Kota Semarang - Erisa Aprilia Wicaksari; Vini Wiratno Putri; Vitradesie Noekent (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Social integration is a unitary condition of living together from various socio-cultural system units, ethnic groups and communities to interact and work together. Social integration as a reflection of the quality of this relationship, if applied to business actors, will increase the value chain for their business. So that the purpose of implementing this program is to create superior milkfish products through the creation of "Social Integration Empowerment" for business groups in Semarang City through the establishment of "Semarang Milkfish Industrial Community". So it is hoped that it can develop synergy between entrepreneurs and community support for the creation of superior products in the region. The program implementation method begins with an integration process to form the Semarang Milkfish Industry community. Then analyze the problems being faced by the community through action research. The next step is to organize meetings which will be followed by building a common understanding, so that the problems that will be handled can be ascertained. Based on these problems, the team and the community will test the action/work program that will be carried out together. After the mutually agreed work program is implemented, the next stage is evaluation and reflection.